Learnings from over a decade of increasing pesticide resistance in the redlegged earth mite, Halotydeus destructor (Tucker). Issue 6 (12th March 2021) - Arthur, Aston L; Maino, James; Hoffmann, Ary A; Jasper, Moshe; Lord, Alan; Micic, Svetlana; Edwards, Owain; van Rooyen, Anthony; Umina, Paul A
Abstract: BACKGROUND: The redlegged earth mite, Halotydeus destructor (Tucker), is a destructive and economically important pest of winter grain crops and pastures in Australia. It is largely controlled by pesticides, but this mite has evolved resistance to pyrethroid and organophosphate chemicals. A national Resistance Management Strategy has been developed for pro‐active management to delay further resistance evolution, though its success is reliant on a detailed understanding of the incidence, patterns of spread, current distribution and the nature of resistance in the field. Here, we report on a long‐term resistance surveillance programme undertaken between 2006 and 2019 informed by resistance risk forecasting. RESULTS: By mapping the Australian distribution of resistance through time, we show that resistance is present across three Australian states and covers more than 3000 km. This current range includes a recently identified population exhibiting organophosphate resistance representing the most easterly location of resistance in H. destructor . Using field history information, we identify associations for the first time between crop management practices employed by farmers and the presence of pyrethroid resistance. Management strategies that could minimize the risk of further resistance include limiting local spread of resistance through farm hygiene practices, crop rotations and reducing pesticide usage. CONCLUSION: This study highlights the challenges of resistance in H. destructor but also indicates how quantitative resistance risk analysis can be developed to target field surveillance and delay further resistance. The management strategies highlighted in this study can help maintain the effectiveness of control options but will depend on farmer engagement and adoption. © 2021 Society of Chemical Industry. Abstract : Pesticide resistance in Halotydeus destructor has emerged over a wide geographic area in Australia. Associations between crop management practices and resistance are identified, which will aid future resistance management efforts.